State-rescaling and re-designing the material city-region: Tensions of disruption and continuity in articulating the future of Greater Manchester. (January 2020) - Hodson, Mike; McMeekin, Andrew; Froud, Julie; Moran, Michael
In a context of globalisation, the emergence of city-regions and the politics and dynamics of their constitution has been debated for almost two decades. Recent writings have extended this focus to seeing city-regions as a geopolitical project of late capitalism where the state takes a critical role in the re-design of city-regions to make them amenable to international competition and to secure strategic inward investments in the built environment and infrastructure. We explore this issue in the context of state redesign of sub-national space in England and focus on Greater Manchester, as the de facto exemplar of 'devolution' to English city-regions. We argue that though re-scaling in Greater Manchester is a long-term historical process this has been punctuated by the UK state's process of 'devolution' since 2014, this has involved a re-design and formalisation of Greater Manchester's governing arrangements. It has also involved invoking a long dormant role for city-regional planning in articulating the future design of the material city-region over the next two decades as an attempt to formalise and continue a pre-existing, spatially selective growth trajectory by new means. Yet, the disruption of new hard governing arrangements also provides challenges to that trajectory. This produces tensions between, on the one hand, the pursuit of a continuity politics of growth through agglomeration, material transformation of the city-region and narrow forms of urban governance and, on the other hand, a more disruptive politics of the future of the city-region, its material transformation and how it is governed. These tensions are producing new political possibilities and spaces in the transformation of Greater Manchester. The implications of this are discussed.